OPTIMALISASI PATROLI SATUAN SABHARA DALAM MENCEGAH TINDAK PIDANA PENCURIAN KENDARAAN BERMOTOR DI WILAYAH HUKUM POLRESTA CIREBON - Wahyu Dwi Mangundiharjo Mangundiharjo (Advances in Police Science Research Journal, 2020)
This research was behind the rise of the theft of motorised vehicles in Cirebon's Polresta. The efforts by the Sabhara unit have not resolved the problem because the number of criminal acts continues to increase. Thus, the most effective effort is to perform a review of the Sabhara patrol Unit. Therefore, research aimed at knowing, the ability of personnel of the Sabhara Patrol Unit, method used in preventing Curanmor, the intensity of patrol implementation based on a qualitative approach, as well as the method of patrol used and the factors that cause of theft of motor vehicles. This research is done with a qualitative approach, using descriptive analysis research methods, as well as data collection techniques with interviews, observations, and document study. The results found that patrol activities in order to suppress the theft of motor vehicles. Figures and prevent the emergence of opportunities and intentions for perpetrators of criminal acts are considered not optimal. Analysis of the ability of officers with the concept of the theft of motor vehicles and management theory and crime prevention theory shows the optimal ability of officers with the fulfillment of several indicators existing assessment of each concept and theory. There are several factors that affect, the contributing factor is the support factor of other functions and optimizing the performance of the Sabhara unit in the prevention of crimes, while the inhibitory factor is the human resources, budget factors, facilities and infrastructure factors, as well as the trust of the community to the police are lacking and individuals who are not wary of surrounding hazards. Based on the results of the research, the authors suggest that the development of member capabilities, fulfillment of facilities and infrastructure, to provide the right method of patrol implementation based on quality and quantity, and to find the cause of curanmor and establishing good cooperation with the community to improve the Community trust.